2023
DOI: 10.1007/s00394-023-03140-w
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Energy Drinks among Italian University students: a cross-sectional multicenter study

Abstract: Purpose The aim of the study was to evaluate the caffeinated Energy Drinks (EDs) consumption among a large sample of Italian undergraduates and its association with some of the major lifestyle risk factors. Methods Students attending twelve public Italian universities were involved between October 2021 and May 2022. Information on socio-demographic characteristics, ED consumption, and on health-related behaviors of participants was collected by the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Once again, the results demonstrated how unhealthy behaviors are interconnected and how one behavior may influence or predict another 67 . These data reinforce that the co-occurrence of multiple unhealthy factors is a widespread problem 68 , 69 , and the complex interplay between different behaviors when developing public health strategies and policies must be acknowledged, as well as that interventions simultaneously targeting multiple risk behaviors may be more effective in promoting overall health and well-being. In the meta-analysis conducted by Meader et al to explore the effectiveness of multiple risky behavior interventions, the authors concluded that non-pharmacologic interventions, i.e., education and skills training, resulted in small reductions in unhealthy behaviors and meaningless reduction in risk of overall mortality 70 .…”
Section: Discussionmentioning
confidence: 53%
“…Once again, the results demonstrated how unhealthy behaviors are interconnected and how one behavior may influence or predict another 67 . These data reinforce that the co-occurrence of multiple unhealthy factors is a widespread problem 68 , 69 , and the complex interplay between different behaviors when developing public health strategies and policies must be acknowledged, as well as that interventions simultaneously targeting multiple risk behaviors may be more effective in promoting overall health and well-being. In the meta-analysis conducted by Meader et al to explore the effectiveness of multiple risky behavior interventions, the authors concluded that non-pharmacologic interventions, i.e., education and skills training, resulted in small reductions in unhealthy behaviors and meaningless reduction in risk of overall mortality 70 .…”
Section: Discussionmentioning
confidence: 53%